2005
DOI: 10.1302/0301-620x.87b7.15586
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of fixed flexion deformity following total knee replacement

Abstract: We investigated fixed flexion deformity (FFD) after total knee replacement (TKR). Data relating to 369 cruciate-retaining unilateral TKRs performed at a single institution were collected prospectively. Fixed flexion was measured pre-operatively and at one week, six months, 18 months, three years and five years after surgery. Using binary logistic regression, pre-operative FFD was a predictor of post-operative FFD > 10 degrees at one week (p = 0.006) and six months (p = 0.003) following surgery. Gender was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 10 publications
6
45
0
2
Order By: Relevance
“…However, these results should be compared with other designs of prosthesis. In addition, the 12-month investigation may not have been adequate to observe resolution of flexion contracture in a majority of patients [22]. Finally, the difference between the groups for distal femoral cut angle, even if statistically significant, has to be modulated by the accuracy of the navigation system, which is less than 1° [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these results should be compared with other designs of prosthesis. In addition, the 12-month investigation may not have been adequate to observe resolution of flexion contracture in a majority of patients [22]. Finally, the difference between the groups for distal femoral cut angle, even if statistically significant, has to be modulated by the accuracy of the navigation system, which is less than 1° [20].…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have reported on knees with large flexion contracture [12,22,23] compared to a "normal" population. The original Knee Society score, prior to the Insall modification of 1993, considered flexion contracture of 0-4°as normal [24].…”
Section: Discussionmentioning
confidence: 99%
“…Aderinto et al observed that the presence of a preoperative fixed flexion deformity was a good predictor for the development of post-operative fixed flexion deformity [21]. Moreover, they showed that postoperative flexion contractures improve with conservative management during the first three years.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported that the condition does not improve postoperatively [17][18][19][20], other investigators have shown gradual recovery with conservative management [19,[21][22][23][24]. It has been well established that the presence of a preoperative flexion contracture increases the risk of developing a postoperative flexion contracture [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation